Designing a model of the role of social media in crisis management and digital supply chain resilience - Farhad Jahangiri; Abolfazl Danaei; Mahsa Akbari; Younos Vakil Alroaia (مدیریت بهره وری)
Abstract The purpose of this research is to design a model of the role of social media in the resilience of the digital supply chain in critical situations. In the qualitative phase of the current research, the data were collected from a purposive sample of 10 experts. Given the limited number of qualified individuals, the entire population of experts was included in the study. In the quantitative phase, the target population comprised 500 employees of MAPNA Company. Using Cohen's table for sample size determination, a sample of 189 participants was selected. This research employs a fundamental-applied approach and follows an exploratory mixed-methods design, integrating both qualitative and quantitative data. The data collection method was based on survey research and the data collection instuments included interviews and questionnaires, the content validity of which was confirmed by experts, and their reliability was calculated using Cronbach's alpha coefficient. In the qualitative part of the study, meta-composite method and foundation data were used, through which 118 open codes, 43 central codes and 13 selective codes have been extracted in five general categories: causal conditions, contextual conditions, intervening conditions, strategies and consequences. Causal conditions include 2 selected codes, 8 concepts and 21 open codes, contextual conditions include 3 selected codes, 10 concepts and 25 open codes, intervening conditions include 2 selected codes, 7 concepts and 21 open codes, strategies include 2 selected codes, 7 concepts and 19 open codes, and consequences include 4 selected codes, 11 concepts and 32 open codes, which are the components of the paradigm model regarding the role of social media in the resilience of the digital supply chain in critical conditions. Based on the output of the structural equations of the initial research model, its validity has been confirmed and the prioritization of the components of the mentioned model has been determined by a radar diagram of the research model. In this regard, technology risk tolerance was ranked first, liquidity cycle was ranked second, and collaboration and outsourcing were ranked third. Key Words: resilient supply chain, digital supply chain, social media 1.Introduction Social media has dramatically changed the way organizations interact and communicate with customers. Digital media and the provision of cheap access to social networks have brought many opportunities and achievements for businesses. Undoubtedly, with reducing the cost of accessing audiences and customers, increasing the speed, accuracy and quality of communication, providing the possibility of more accurate measurement of the effectiveness of activities, the possibility of better and more effective management of crises, and in general, increasing the power of businesses in the fields of work, providing opportunities for taking ownership of a media can be very useful and effective in the success of today's organizations and businesses, and without a doubt, social networks and similar channels have provided them with a variety of tools, applications, and developers in order to advance the supply of various tools. Considering the significant impact that social media has on life and business processes in the third millennium and the rapid and impressive developments of information and communication technology in recent decades, significant and in some cases fundamental changes have been made in various relationships of today's societies. 2.Literature Review In today's world, changes in the economy and industry are happening at a faster rate than in the past. Due to globalization, countries are ingreasingly experiencing heightened levels of competition. Given the importance of supply chains and their effective management in creating competitive advantages, it is often said that competition between organizations has been replaced by the competition between supply chains. As a result, organizations are trying to improve their supply chain management to gain sustainable competitive advantages (Lee et al., 2018). Achieving this requires a fundamental transformation within the organization. Given the importance of conducting this research, coupled with the instability of conditions and significant changes in work processes, it is necessary for organizations to adapt the scope of their supply chain so that they can develop optimal strategies to stay at the top of the competition in volatile conditions. Therefore, it is necessary for them to maintain their resilience in the mentioned conditions and be equipped with working methods suitable for the age of technology and new technologies (Singh et al., 2017). In other words, considering the significant impact that social media has on the processes of life and business in the third millennium and the rapid and impressive developments of information and communication technology in recent decades, there have been significant and in some cases fundamental changes in various relationships of today's societies (Labafi, 2018); Organizations and their communications have changed and the demands and expectations of customers have undergone many changes. Knowing the fact that the use of digital technologies in processes creates competitive advantages for businesses and organizations (Samizadeh, 2020), we can conclude that the implementation and use of the digital supply chain is undoubtedly a significant option for organizations and businesses. This work aimed to minimize financial and time costs while enhancing productivity in the production process until the final delivery of goods and services to customers (Azer & Khorrami, 2021). By comparing the key features of the digital supply chain with the traditional supply chain, it can be seen that the results of the presence of digital technologies in the supply chain processes for organizations and businesses will be brilliant and efficient beyond imagination (Mehrabi, 2016). The smallest disruption in the process of a supply chain can be likened to a fault. A fault whose gap and depth can increase moment by moment (Manogran et al., 2018). 3.Methodology In the present study, the researcher sought to provide a model for the role of social media in the resilience of the digital supply chain in critical conditions. In this research, the metacomposite method has been used to present the model. In the qualitative part of the study 10 experts participated through the whole number selection, and the quantitative part included 500 employees of MAPNA company, based on Cohen's sample size table. The investigation began with an extensive review of the related existing literature (referring to documents and five non-Iranian databases of ScienceDirect, Web of Science, Google Scholar, Scopus, Emerald, and three Iranian databases CIVILICA, Magiran and SID). The total number of articles found considering the input criteria was 163 studies (Persian and English). After reviewing all the studies and evaluiating them based on content criteria and accessibility, the final results were extracted from 19 studies (14 English studies and 5 Persian studies) which were reviewed and analyzed. Then, in order to confirm the extracted factors, an interview was arranged with the relevant experts (including experts and specialists of the digital supply chain and social media and top managers of MAPNA Company) and the importance coefficient of each factor was determined. 4.Result According to the results, 118open codes, 43 central codes and 13 selective codes were extracted. Thirteen selective codes of the study were placed in five general categories including causal conditions, contextual conditions, intervening conditions, strategies and consequences. Causal conditions include 2 selected codes, 8 concepts and 21 open codes, contextual conditions include 3 selected codes, 10 concepts and 25 open codes, intervening conditions include 2 selected codes, 7 concepts and 21 open codes, strategies include 2 selected codes, 7 concepts and 19 open codes, and the consequences include 4 selected codes, 11 concepts and 32 open codes, which are the components of the paradigm model regarding the role of social media in the resilience of the digital supply chain in critical conditions. Based on the output of the structural equations of the initial research model, its validity has been confirmed and the prioritization of the components of the mentioned model has been determined by a radar diagram of the research model. In this regard, technology risk tolerance was ranked first, liquidity cycle was ranked second, and collaboration and outsourcing were ranked third. 5.Conclusion According to the obtained results and the importance of the topic under study, the role of social media and the implementation of digital transformation in organizations as an undeniable competitive advantage has been noticed by senior managers of organizations and businesses. Digitalization of the supply chain will bring revolutionary changes. New technologies such as big data, cloud computing, and the Internet of Things can help solve these problems. In fact, digitization can enhance supply chain visibility and the use of advanced digital technologies enables modularization, simplicity and standardization of products and processes. Companies must recognize the benefits of innovative business models that add value to their product portfolio and create new demand channels for more digital customers. In fact, investing and deploying new technologies by increasing access to information, reducing costs, improving product quality, and increasing responsiveness and collaboration capabilities provide a long-term competitive advantage for business supply chains even in critical situations. Conflict of interest: none